Pengaruh Pengetahuan Investasi, Toleransi Risiko Dan Pengaruh Sosial Terhadap Keputusan Investasi Generasi Muda Di Kota Bengkulu - Ratna Rutiningsih; Yun Fitriano; Denis Rydarto (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
An investment decision is the process of selecting and allocating funds or resources to an asset or project with the primary goal of achieving future financial returns. This process involves considering various factors. This study aims to determine whether investment knowledge, risk tolerance, and social influences partially or simultaneously influence the investment decisions of young people in Bengkulu City.The approach used in this study was quantitative, using a survey method, which utilizes mathematical models, theories, and/or hypotheses related to natural phenomena. The sampling technique used was purposive sampling. The researcher selected the sample based on certain criteria, namely young people residing in Bengkulu City with experience or interest in investing.There was an effect (X1) on investment knowledge with a significance value (sig) of 0.000 <0.05. The correlation value (t-count) > t-table (0.561 > 0.195), thus Ho was rejected and Ha was accepted. The significance value obtained indicates that variable X influences investment decisions (Y). Risk Tolerance (X2) with a significance value of 0.068 which is slightly below 0.10, the t-count correlation value of 0.193 is just below the t-table of 0.195, this indicates that statistically the influence of risk tolerance has no effect. There is an influence (X3) of social influence on investment decisions with a significance value of 0.002 <0.10 and t-count>t-table (0.418>0.195). Investment knowledge, risk tolerance and social influence together have a significant positive effect on investment decisions of the younger generation with an F-count value of 43.429 and a significance of 0.000 <0.05 which is much smaller than F-table (df 3, 96) of around 2.70.